Learning Geriatric Medicine A Study Guide for Medical Students (Practical Issues in Geriatrics,, 2018)
This textbook presents hands-on training material for medical students. The style reflects the need for practice-based teaching with a modern edge in daily clinical routine; accordingly, it also employs online material and pocket cards. Each chapter begins with specific learning objectives, which are cross-referenced with the European curriculum for undergraduate medical education released by the European Union of Medical Specialists (UEMS) together with the European Union Geriatric Medicine Society (EUGMS), as well as the minimum geriatric competences for medical students established by the American Geriatrics Society (AGS). World-renowned European experts in practicing and teaching the interdisciplinary field of Geriatrics contributed to this work, with the aim of offering the new generation of health professionals a global perspective on one of the greatest public health challenges of our time: the management of the steadily increasing number of older, multimorbid, and vulnerable persons. The major strength of this book - published under the auspices of the EUGMS - is its pragmatic, goal-oriented approach, which makes it suitable for bedside learning and patient-centered medicine; further, all of the chapters are firmly based on the pillars of the ageing process in all of its biological aspects, helping readers understand the pathophysiology of and rationale behind interventions for the main geriatric syndromes and disorders.